Placing Security and Rule of Law on the Development Agenda - Schneider, Mark L. (World Bank, 2012)
The International Crisis Group has recognized the need for simultaneity rather than sequencing in security and development to contribute to conflict prevention, end conflict where it exists, and help ensure the success of post conflict reconstruction and stabilization.